O conceito de Transferência na Psicoterapia Analítica Funcional - Alarcão, Heric Ribeiro de (Universidade Federal do Tocantins, 2024)
This article aims to demonstrate how the Freudian conception of Transference was integrated into Functional Analytic Psychotherapy through operationalization in behavioral terms, delineating the similarities and differences between the theoretical understanding and clinical management of these approaches regarding the transferential phenomenon. The method used was a literature review of books and psychology journals by key authors in Psychoanalysis (Freud) and Functional Analytic Psychotherapy (Kohlenberg and Tsai), as well as others that delve into complementary and pertinent subjects for the discussion, seeking to capture a general and suitable idea about Transference and its implications. The results highlight theoretical differences about transference but, at the same time, show many similarities in how the phenomenon presents itself in clinical practice. Regarding clinical management, the data emphasize that the approaches mainly differ in the therapists' attitude towards the transferential episode. Finally, we discuss the influence of scientific isolation on the idea that certain areas are irreconcilable and have nothing to contribute to each other, an unproductive belief that hinders not only integrative dialogue but also the entire field of psychotherapy studies.